“The Angolan first!” How opposition MPs represent constituencies in the multiparty Angolan parliament (2008-2022) - Sá, Ana Lúcia (ASAUK Biennial Conference 2022, 2022)
Multiparty parliaments in authoritarian regimes are believed to have limited policy influence and to be privileged floors for co-optation strategies of the autocrat or the dominant party. The Angolan National Assembly fits this model. Angola is a presidential system with a closed-list proportional representation electoral system and a weakly institutionalized parliament where the legislative performance is limited to the dominant party (People’s Movement for the Liberation of Angola, MPLA). However, the National Assembly is the only institution in which opposition parties can publicly perform their top-rank political tasks due to their absence in executive power. Who composes the opposition political elite in Angola? How does the opposition political elite behave in the parliament and mobilize their constituencies' interests at the parliamentary level? To answer these questions, we combine novel biographical data on the opposition parties’ candidates with parliamentary activity data (e.g. questions, speeches etc.) focusing on the post-civil war legislatures (2008, 2012 and 2017). During this period, newcomers (such as the Broad Convergence for the Salvation of Angola – Electoral Coalition, CASA-CE) burst onto the political scene and joined historical opposition parties (such as the National Unit for the Total Independence of Angola, UNITA) in parliament. The data allow us to explore MPs biographic background, and how connected they are with their constituencies, over time and across electoral cycles. This paper contributes to the literature on MPs' behaviour and opposition elite formation in resilient authoritarian regimes with a dominant party system.